(3QSGdI aj GdHhds - (3eLghds
(3ChdgG (B:s
(3HSe Gddg fHOC HYhf Gddg hMSf Jhajbg HLhGeY eG bGdg LGdjfhS aj GdHhd ; GdCTjGA GdJj jJe HgG chf GdEfSGf KdGKI hcdgG MGQ hgj gPg (B: (3GdOe , GdQhM , Gdefj s
(3BNQgG (B:s
(3hGdWHjYI JgXe Hhd Gddjd gVeG MSfG cMGd YGOJgG Hfhe Gddjd hJgVe HGdfgGQ VeG jSjQ GdbdI YGOJgG HOh Pdc GfgG eJYhOI Cf JYgVe HGdfhe adPdc gVeJ Hfhe GdfgGQ hdcfgs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdWHs